2021
DOI: 10.3390/met11091369
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Copper from Waste-Printed Circuit Boards (PCBs) in Sulfate Medium Using Cupric Ion and Oxygen

Abstract: In the present paper, the leaching of copper from printed circuit boards (PCBs) using sulfuric acid with Cu2+ and O2 is proposed. The effects of various process parameters such as agitation speed, temperature, the type and the flow rate of gas, initial Cu2+ concentration, and pulp density were investigated to examine the dissolution behavior of Cu from PCBs in 1 mol/L sulfuric acid. The kinetic studies were performed using the obtained leaching data. The leaching rate of Cu from PCBs was found to be higher on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…In addition to the kinetics study performed, this showed that process is governed by a mixed control (diffusive and chemical), as in Figure 5 and Figure 7 . It was evident that the hydrodynamic and thermodynamic variables affected the leaching of copper, while the value of the activation energy (E a ) was 25.78 kJ/mol, corroborating the mixed chemical–diffusive control for the leaching kinetics, which was quite similar (23.8 kJ/mol) to that obtained during the leaching of Cu from WPCBs in sulfate medium using cupric ions and oxygen [ 37 ]. This confirmed that the studied system studied is valid for leaching the Cu contained in these kind of residues, without the need to add oxidants such as HNO 3 , H 2 O 2 , Cu 2+ , or Fe 2+ .…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In addition to the kinetics study performed, this showed that process is governed by a mixed control (diffusive and chemical), as in Figure 5 and Figure 7 . It was evident that the hydrodynamic and thermodynamic variables affected the leaching of copper, while the value of the activation energy (E a ) was 25.78 kJ/mol, corroborating the mixed chemical–diffusive control for the leaching kinetics, which was quite similar (23.8 kJ/mol) to that obtained during the leaching of Cu from WPCBs in sulfate medium using cupric ions and oxygen [ 37 ]. This confirmed that the studied system studied is valid for leaching the Cu contained in these kind of residues, without the need to add oxidants such as HNO 3 , H 2 O 2 , Cu 2+ , or Fe 2+ .…”
Section: Discussionsupporting
confidence: 58%
“…However, for the leaching of Cu, no work has been carried out using this leaching system. The most closely related works on the leaching of Cu have used ammonium and Cu 2+ , or ammonia−ammonium sulfate [ 37 , 42 ]. For this reason, the present work is of importance due, principally, to the use of a non-toxic reagent, which was used directly without the addition of an oxidant like HNO 3 , H 2 O 2 , O 3 , Cu 2+ , or Fe 2+ .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While significant work has been reported on the hydrometallurgical recovery of metals from PCBs using HNO3, HCl, H2SO4, and aqua-regia, aqua regia, is popular for the determination of the initial Cu content of PCB samples and has been observed to demonstrate excellent efficiency in Cu leaching than other leach solutions [38][39][40]. It was important to determine the initial Cu content of the PCB to have a reference to which the efficiency of the test leach solution (mixture of malonic acid and H2O2) can be compared.…”
Section: 2mentioning
confidence: 99%